Predicting and grading the degree of difficulty of cochlear implant surgery by evaluating temporal bone using high resolution computed tomography and magnetic resonance imaging - Chemburkar, Vipul V.; Saluja, Gagandeep S.; Shetty, Devdas S.; Agrawal, Ruchi R. (International Journal of Research in Medical Sciences, 2019)
Background: The current study was designed to assess the challenges that arise during cochlear implantation. Hence imaging based grading system, using a structured, 12-point scoring chart was developed with an aim to assess various anatomical factors of temporal bone helpful in contemplating complications involved in surgery and to assess various congenital and acquired abnormalities if detected during scan which can affect cochlear implant surgery. Methods: This was a descriptive study done on 60 patients with sensorineural hearing loss. They were evaluated preoperatively by using HRCT and MRI findings and subsequently underwent cochlear implantation. A 12-point scoring chart was developed based on imaging findings. Surgical times were noted in each case and each imaging point on the scoring chart was correlated with the surgical times. Results: Eleven out of 12 points in the scoring chart proved to be statistically significant in predicting the degree of difficulty of the surgical procedure. One point was not correlating with the surgical timings. Based on the grading system, in the present study, there were 37 patients (61.66%) classified as Grade 1, 16 patients (26.67%) classified as Grade 2 and 7 patients (11.67%) classified as Grade 3. Conclusions: These radiological image findings and its related grading system are relatively easy and quick to assess on readily available pre-operative temporal bone CT scan and MRI. They can form a pre-operative checklist that provides a formalized approach for the surgeons and, in particular surgical trainees, predict and, thus prepare for, potentially challenging cochlear implant cases.